Co‐seismic landslides in the Sikkim Himalaya during the 2011 Sikkim Earthquake: Lesson learned from the past and inference for the future. Issue 12 (2nd March 2022) - Joshi, Mayank
Abstract : Sikkim, a north‐eastern state of India, has a very specific and unique place in the tourism map of India. Every year, lakhs of people visit the state. To accommodate such floating population in the area, some big towered home stays/hotels have been constructed. However, the area is under the threat of many natural disasters such as earthquake, landslide, land subsidence, cloudburst, etc. In the year 2021, within a span of 8 months (April–November), the Sikkim state hosted four light to moderate earthquakes (Mw 4.1–Mw 5.1). Out of these, the strongest earthquake (Mw 5.1) occurred on 5 April 2021, which was well experienced in the parts of Indian states (i.e., Sikkim, West Bengal, Bihar) and across International borders, viz Bangladesh, Nepal, Bhutan, and China. Fortunately, this earthquake did not cause any major damage in the region. However, in the last two decades, one moderate (Mw 5.3) and one strong earthquake (Mw 6.9) has occurred in the Sikkim region on 14 Feb 2006 and 18 September 2011, respectively. Both of these earthquakes caused well enough damage to the residential as well as commercial buildings. Apart from infrastructural degeneracy, the 2011 Sikkim Earthquake (Mw 6.9) also caused generation of co‐seismic landslides within ~100 km epicentral distance from the earthquake. After a decade, from the 2011 earthquake, Gangtok city and other parts of the state have been rebuilt and reconstructed again, but most of the newly constructed and old refurbished buildings are established in the steep slope areas without considering the geotechnical properties of the underlying soil. These structures could be vulnerable during moderate to strong earthquakes. Therefore, the present study unfurled a question "Did we learn any lesson from the 2011 Sikkim Earthquake?". Furthermore, the study calls for earthquake hazard adaptation measures in the tectonically sensitive Himalayan region in order to safeguard the lives and vital infrastructure. Abstract :